The functions of social indicators in the elaboration of public policy proposals. Case study: Public health policies - Rus, Mihaela; Tasențe, Tănase; Sandu, Mihaela Luminița; Badea, Monica Mădălina (Technium Social Sciences Journal, 2022)
The identification and measurement of social indicators are essential elements in defining the public issue, which represent a first important step for the elaboration of public policies proposals. In this respect, regarding COVID-19 Pandemic public policies strategists, both of National Governments and international organizations measured each social indicator that could be integrated in the program of measures to control SARS-COV-2 virus. Therefore, indicators such as total number or daily number of cases, number of active / closed cases, number of new cases, number of people in ICU, rete of cases per 1 mil. Inhabitants, incident at community, local, national, continental and global level, number of performed tests and so on, were used by public central and local administrations in order to apply the measurements for fighting the pandemic. In this paperwork we aim to measure social perception on the efficiency of public health policies elaborated and deployed by Romanian Government, as well as the degree of transparency in communication of the public institutions in relationship with citizens.